Feasibility of Remote Performance Assessment Using the Free Research Executive Evaluation Test Battery in Adolescents - Segura, Isis Angelica; Pompéia, Sabine (Frontiers in Psychology, 2021)
Lockdowns and other preventive measures taken to curb the spread of diseases such as COVID-19 have restricted the use of face-to-face cognitive assessment. Remote testing may be an alternative, but it should first be shown to be comparable to in-person assessment before being used more widely, during and after the pandemic. Our aim was to evaluate the suitability of online, examiner-mediated administration of an open-access battery of executive function tests (the Free Research Executive Evaluation battery, or FREE) that can be adapted considering various characteristics of diverse populations and therefore used worldwide. A total of 96 9–15-year olds (42 girls) were tested, half of whom online through video calls mediated by an examiner. Their performance was compared to that of the other 48 individuals tested face-to-face, who were matched against the online-tested participants for age, pubertal status, sex, and parental schooling. The battery consists of two tests of the following executive domains: Updating (2-Back and Number Memory tests), Inhibition (Stroop Victoria and Stroop Happy-Sad), and Switching (Color Shape and Category Switch). Answers were vocal and self-paced, and the examiner recorded accuracy and time taken to complete in-person and online tasks. Only free software is needed for the assessment. Executive measures obtained from the tasks did not differ statistically between online and in-person tested participants and effects sizes of group effects were small, thus showing that the FREE test battery holds promise for online cognitive assessment, pending confirmation in different samples and further validation studies.